(untitled) (Bangladesh Journal of Neurosurgery, 2023)
Background: The incidence of atypical clinic-radiological presentations of spinal TB is on the upsurge. Lesions that share similar features should be evaluated thoroughly. Tissue diagnosis remains the only foolproof investigation to confirm diagnosis before initiation of treatment. Methods: We present 2 cases who were provisionally diagnosed as a case of Tubercular spondylodiscitis based on clinic-radiological findings. After failure of response from anti tubercular drugs, they underwent operative management for decompression of neural elements and histological confirmation of the provisional diagnosis. Results: Clinical features like back pain, weight loss, gait abnormalities with radiological features like Magnetic resonance imaging and GeneXpert, CT guided FNAC helps in early detection and initiation of treatment of spinal TB. But in our case, 58year old female and 13 years old male presented with clinic-radiological features consistent with Spinal TB. Histopathology and immunohistochemistry confirm that first case is due to Aspergillus Spinal Epidural Abscess (ASEA) and second case due to round blue cell neoplasm consistent with Ewings Sarcoma. Conclusion: This article highlights the importance of awareness of the different clinic-radiographic features of spinal lesions, which can mimic a Tubercular Spondylodiscitis. In order to avoid delayed diagnosis, clinicians must be aware of differential diagnosis from common to rare entity which may interfere with other clinical conditions. Bang. J Neurosurgery 2022; 12(1): 29-36